Cloud data secure deduplication scheme via role-based symmetric encryption - Jinbo XIONG; Yuanyuan ZHANG; Youliang TIAN; Zuobin YING; Qi LI; Rong MA (Tongxin xuebao)
The rapid development of cloud computing and big data technology brings prople to enter the era of big data,more and more enterprises and individuals outsource their data to the cloud service providers.The explosive growth of data and data replicas as well as the increasing management overhead bring a big challenge to the cloud storage space.Meanwhile,some serious issues such as the privacy disclosure,authorized access,secure deduplication,rekeying and permission revocation should also be taken into account.In order to address these problems,a role-based symmetric encryption algorithm was proposed,which established a mapping relation between roles and role keys.Moreover,a secure deduplication scheme was proposed via role-based symmetric encryption to achieve both the privacy protection and the authorized deduplication under the hierarchical architecture in the cloud computing environment.Furthermore,in the proposed scheme,the group key agreement protocol was utilized to achieve rekeying and permission revocation.Finally,the security analysis shows that the proposed role-based symmetric encryption algorithm is provably secure under the standard model,and the deduplication scheme can meet the security requirements.The performance analysis and experimental results indicate that the proposed scheme is effective and efficient.